Longitudinal changes in vigorous intensity physical activity from childhood to adolescence: Gateshead Millennium Study. Issue 4 (April 2019) - Beltran-Valls, Maria Reyes; Janssen, Xanne; Farooq, Abdulaziz; Adamson, Ashley J.; Pearce, Mark S.; Reilly, Jessica K.; Basterfield, Laura; Reilly, John J.
Abstract: Objective: The aims of our study were to quantify levels and investigate sex-specific changes and trajectories in VPA longitudinally from age 7 to 15 years. Design: Longitudinal observational study. Methods: Participants were part of the Gateshead Millennium Study. Measures were taken at age 7 (n = 507), 9 (n = 510), 12 (n = 425) and 15 years (n = 310). Vigorous physical activity was quantified objectively using ActiGraph GT1 M accelerometers over 5–7 days at the four time-points. Multilevel linear spline random-effects model and trajectory analysis to identify sub-groups were performed. Results: In boys, average VPA declined across childhood followed by an increase at adolescence, while in girls, average VPA declined across the 8-year study period. In boys, daily VPA decreased from 9-12 years (1.70 minutes/year) and increased from 12-15 years (1.99 minutes/year) (all p < 0.05). In girls daily VPA decreased from 7-9 years (1.70 minutes/year) (p < 0.05). Three VPA trajectories were identified which differed between the sexes. In boys, one group decreased from an initial relatively high level, one group, initially relatively low, increased, whereas the third one was stable over the 8-year period. In girls, all three groups declined from baseline. Conclusions: Marked sex and age-specific trajectories in VPA change were observed. These novel findings should help sports and exercise medicine specialists, as well as policy makers, in their effort to maintain or increase VPA in childhood and adolescence.